Study on the passively mode-locked fiber laser with different cavity dispersion - Ye, Jin. (2012)
Soliton is a nonlinear wave which has the properties of propagating without change of its properties (shape, velocity etc) and stable against mutual collisions and retains their identities. Nowadays solitons are becoming a more and more important development in the optical communications field.